Effect of Seed Category as Affected by Bipolaris sorokiniana on the Germination of Wheat Seeds (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted under in-vitro condition to determine the effect of wheat seed categories such as healthy looking, blackpointed and shriveled as affected by Bipolaris sorokiniana on the germination of wheat seeds. The work was done in the   laboratory of Seed Pathology Center, Bangladesh Agricultural University, Mymensingh during 2010-11. The highest prevalence   65%) of B. sorokiniana was recorded in shriveled seeds, (42%) was recorded in blackpointed seeds, and (30%) was associated  with healthy looking seeds. The pathogen was responsible for the highest germination failure (87%) found in the category of   shriveled seeds and then (35%) was found in blackpointed seeds while the healthy looking seeds showed (24%) germination  failure. The result suggests that, the shriveled and blackpointed seed samples must be rejected, and after proper seed health test in an only the healthy looking seeds may be recommended for sowing through proper seed treatment. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11563 J. Environ. Sci. & Natural Resources, 5(1): 113 - 116, 2012